Positive electrode lithium supplement additive and its application, positive electrode sheet, lithium-ion battery
By covering cobalt sulfide or molybdenum sulfide in lithium orthopedic lithium additive additive surface, the problem of lithium ion battery during the first charging process is solved, and the battery capacity maintenance rate and electrochemical performance are improved.
Patent Information
- Application Number
- CN202411377084.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-30
- Publication Date
- 2025-01-24
- Estimated Expiration
- 2044-09-30
AI Technical Summary
During the first charging process of lithium-ion batteries, the consumption of lithium in the positive electrode material leads to low efficiency of the first cycle, reducing the capacity and energy density of the lithium-ion battery.
The lithium iron is used as a lithium additive, and sulfides or molybdenum disulfide or sulfide of the cobalt is covered on its surface.
The capacity maintenance rate and electrochemical dynamic performance of lithium -ion batteries are improved, and the gas production and internal resistance of the battery are reduced.
Smart Images

Figure CN118899561B_ABST
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of batteries, and in particular to a positive electrode lithium supplement additive and application thereof, a positive electrode sheet, and a lithium ion battery. Background Art
[0002] There is a common problem in the manufacturing process of lithium-ion batteries: during the first charging process of lithium-ion batteries, the organic electrolyte is reduced and decomposed on the surface of negative electrode materials such as graphite to form a layer of solid electrolyte interface film (SEI), which can effectively inhibit the decomposition of the electrolyte and improve the cycle life of lithium-ion batteries. However, the formation of this SEI film will cause the consumption of lithium in the positive electrode material. This process is irreversible and will cause the first cycle coulomb efficiency to be low, reducing the capacity and energy density of lithium-ion batteries. Pre-lithiation technology can provide additional active lithium for the battery and is considered to be one of the effective strategies to solve the loss of active lithium in high-capacity batteries and improve the cycle life of batteries.
[0003] Lithium ferrite (Li x FeO y , 4.5≤x≤5.5, 3.75≤y≤4.25) are widely used as positive electrode lithium supplement additives because of their good lithium supplement effect. The conventional method for preparing lithium ferrite is to synthesize the lithium ferrite precursor by a high-temperature solid phase method, and then carbon-coat it, or to use an in-situ high-temperature solid phase method to synthesize carbon-coated lithium ferrite in one step. CN110518298A introduces a Co-doped lithium ferrate lithium supplement, but the lithium ferrate synthesized by this method has an unstable interface and high residual alkali. Patent CN114050258A introduces a Li5Fe a M b O4 lithium supplement, in which the element M is one or more of Ni, Co, Mn, and Cu, but this method has the same problem as conventional lithium ferrite, that is, the carbon coating structure is incomplete and cannot be effectively utilized. In addition, the oxygen released by lithium ferrite during the first charge will cause the battery electrolyte to decompose, and excessive gas production will seriously affect the commercial application of lithium ferrite.
[0004] In view of this, the present invention is proposed. Summary of the invention
[0005] The first object of the present invention is to provide a positive electrode lithium supplement additive to solve the above technical problems.
[0006] The second object of the present invention is to provide the use of the above-mentioned positive electrode lithium supplement additive in the preparation of lithium ion batteries.
[0007] The third object of the present invention is to provide a positive electrode sheet.
[0008] A fourth object of the present invention is to provide a lithium ion battery.
[0009] In order to achieve the above objectives, the following technical solutions are adopted:
[0010] In a first aspect, the present invention provides a positive electrode lithium supplement additive, including lithium ferrite;
[0011] The surface of the lithium ferrite is coated with cobalt sulfide or molybdenum disulfide;
[0012] The lithium ferrite includes Li5FeO4;
[0013] The molar ratio of cobalt element to sulfur element in the cobalt sulfide is 1:(0.75-2).
[0014] If the surface of the lithium ferrite is coated with cobalt sulfide, the molar ratio of the lithium ferrite to the cobalt sulfide is 1:(0.006-0.18);
[0015] If the surface of the lithium ferrite is coated with molybdenum disulfide, the molar ratio of lithium ferrite to molybdenum disulfide is 1:(0.004-0.095).
[0016] As a further technical solution, the surface of the lithium ferrite is coated with cobalt sulfide, and the preparation method of the positive electrode lithium supplement additive comprises the following steps:
[0017] a. The lithium ferrite, cobalt acetate and water are mixed, reacted under closed conditions and dried to obtain lithium ferrite coated with cobalt acetate hydroxide;
[0018] b. The lithium ferrite coated with the cobalt acetate hydroxide obtained in step a is mixed with thioacetamide and ethanol for reaction, and after the reaction, the reaction product is sintered under a protective atmosphere to prepare a positive electrode lithium supplement additive.
[0019] As a further technical solution, in step a, the reaction temperature is 75-85°C and the reaction time is 2-4h;
[0020] In step b, the reaction temperature is 110-130°C and the reaction time is 8-12h;
[0021] In step b, the sintering temperature is 550~650℃.
[0022] As a further technical solution, the surface of the lithium ferrite is coated with molybdenum disulfide, and the preparation method of the positive electrode lithium supplement additive comprises the following steps:
[0023] Lithium ferrite, sodium molybdate, thiourea and water are mixed for reaction, and after the reaction, the reaction product is sintered under a protective atmosphere to prepare a positive electrode lithium supplement additive.
[0024] As a further technical solution, the reaction temperature is 200-250°C and the reaction time is 16-24h;
[0025] The sintering temperature is 550-650°C.
[0026] In a second aspect, the present invention provides the use of the above-mentioned positive electrode lithium supplement additive in the preparation of a lithium ion battery.
[0027] In a third aspect, the present invention provides a positive electrode sheet, wherein the active material layer of the positive electrode sheet contains the positive electrode lithium supplement additive.
[0028] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the positive electrode sheet of the lithium-ion battery is the positive electrode sheet described above.
[0029] Compared with the prior art, the present invention has the following beneficial effects:
[0030] The positive electrode lithium supplement additive provided by the present invention has high gram capacity, can effectively reduce the gas production and internal resistance of the battery, and improve the capacity retention rate and electrochemical kinetic performance of the battery. BRIEF DESCRIPTION OF THE DRAWINGS
[0031] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.
[0032] Figure 1 XRD results of Examples and Comparative Examples;
[0033] Figure 2 Electrochemical impedance of lithium iron phosphate soft-pack batteries assembled in Examples and Comparative Examples. DETAILED DESCRIPTION
[0034] The embodiments of the present invention will be described in detail below in conjunction with the embodiments and examples, but it will be appreciated by those skilled in the art that the following embodiments and examples are only used to illustrate the present invention and should not be considered as limiting the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by those of ordinary skill in the art without making creative work are within the scope of protection of the present invention. If specific conditions are not specified, proceed according to normal conditions or conditions recommended by the manufacturer. If the manufacturer is not specified for the reagents or instruments used, they are all conventional products that can be purchased commercially.
[0035] In a first aspect, the present invention provides a positive electrode lithium supplement additive, including lithium ferrite;
[0036] The surface of the lithium ferrite is coated with cobalt sulfide or molybdenum disulfide;
[0037] The lithium ferrite includes Li5FeO4.
[0038] The positive electrode lithium supplement additive provided by the present invention has high gram capacity, can effectively reduce the gas production and internal resistance of the battery, and improve the capacity retention rate and electrochemical kinetic performance of the battery.
[0039] The molar ratio of the cobalt element to the sulfur element in the cobalt sulfide may be, for example, but not limited to, 1:0.75, 1:1 or 1:2.
[0040] If the surface of the lithium ferrite is coated with cobalt sulfide, the molar ratio of lithium ferrite to cobalt sulfide may be, for example, but not limited to, 1:0.006, 1:0.01, 1:0.05, 1:0.1 or 1:0.18;
[0041] If the surface of the lithium ferrite is coated with molybdenum disulfide, the molar ratio of lithium ferrite to molybdenum disulfide is 1:0.004, 1:0.01, 1:0.05 or 1:0.095.
[0042] In some optional embodiments, lithium ferrite can be purchased or prepared by the following method:
[0043] According to the molar ratio of lithium ferrite element, lithium carbonate and ferric nitrate are mixed and ground in water until D90 is less than 150nm to obtain a lithium ferrite precursor aqueous solution, and then the lithium ferrite precursor aqueous solution is spray-dried and air flow-broken to obtain lithium ferrite powder.
[0044] In some optional embodiments, the surface of the lithium ferrite is coated with cobalt sulfide, and the preparation method of the positive electrode lithium supplement additive comprises the following steps:
[0045] a. The lithium ferrite, cobalt acetate and water are mixed, reacted under closed conditions and dried to obtain lithium ferrite coated with cobalt acetate hydroxide;
[0046] b. The cobalt acetate hydroxide-coated lithium ferrite obtained in step a is mixed with thioacetamide and ethanol for reaction (cobalt acetate hydroxide and thioacetamide react to form cobalt sulfide), and after the reaction, the reaction product is sintered under a protective atmosphere to prepare cobalt sulfide-coated lithium ferrite (positive electrode lithium supplement additive).
[0047] The preparation method is simple and convenient; in the prepared positive electrode lithium supplement additive, the sulfide coating on the surface of lithium ferrite is complete and has good bonding strength.
[0048] In some optional embodiments, in step a, the reaction temperature may be, for example, but not limited to, 75°C, 77°C, 79°C, 81°C, 83°C or 85°C, and the reaction time may be, for example, but not limited to, 2h, 3h or 4h;
[0049] In step b, the reaction temperature may be, but not limited to, 110° C., 120° C. or 130° C., and the reaction time may be, but not limited to, 8 h, 10 h or 12 h;
[0050] In step b, the sintering temperature may be, for example, but not limited to, 550° C., 570° C., 590° C., 610° C., 630° C. or 650° C. The sintering is performed to remove moisture from the cobalt sulfide and improve the bonding strength between the cobalt sulfide and lithium ferrite.
[0051] In some optional embodiments, the surface of the lithium ferrite is coated with molybdenum disulfide, and the preparation method of the positive electrode lithium supplement additive comprises the following steps:
[0052] Lithium ferrite, sodium molybdate, thiourea and water are mixed and reacted (sodium molybdate and thiourea react to form molybdenum disulfide), and the reaction product is sintered under a protective atmosphere to prepare lithium ferrite coated with molybdenum disulfide (positive electrode lithium supplement additive).
[0053] The preparation method is simple and convenient; in the prepared positive electrode lithium supplement additive, the molybdenum disulfide coating on the surface of lithium ferrite is complete and has good bonding strength.
[0054] In some optional embodiments, the reaction temperature may be, for example, but not limited to, 200°C, 210°C, 22°C, 230°C, 240°C or 250°C, and the reaction time may be, for example, but not limited to, 16h, 18h, 20h, 22h or 24h;
[0055] The sintering temperature may be, for example, but not limited to, 550° C., 570° C., 590° C., 610° C., 630° C. or 650° C. The sintering can remove moisture from the cobalt sulfide and improve the bonding strength between molybdenum disulfide and lithium ferrite.
[0056] In a second aspect, the present invention provides the use of the above-mentioned positive electrode lithium supplement additive in the preparation of a lithium ion battery.
[0057] The positive electrode lithium supplement additive provided by the present invention has high gram capacity and is used in the preparation of lithium ion batteries, which can effectively reduce the gas production and internal resistance of the battery and improve the capacity retention rate and electrochemical kinetic performance of the battery.
[0058] In a third aspect, the present invention provides a positive electrode sheet, wherein the active material layer of the positive electrode sheet contains the positive electrode lithium supplement additive.
[0059] The positive electrode sheet contains the positive electrode lithium replenishing additive provided by the present invention, and thus has all the beneficial effects of the positive electrode lithium replenishing additive of the present invention.
[0060] In a fourth aspect, the present invention provides a lithium-ion battery, wherein the positive electrode sheet of the lithium-ion battery is the positive electrode sheet described above.
[0061] The battery has high capacity retention rate and good electrochemical kinetic performance.
[0062] The present invention is further described below by means of specific examples and comparative examples. However, it should be understood that these examples are only used for more detailed description and should not be construed as limiting the present invention in any form.
[0063] Example 1
[0064] Preparation of CoSx-coated lithium ferrite
[0065] (1) According to the molar ratio of lithium to iron being 5:1, lithium carbonate and ferric nitrate are fully ground and mixed in 2-3 times the mass of water to make D90 less than 150nm to obtain a lithium ferrite precursor aqueous solution, which is then spray-dried, high-temperature sintered (600°C, 12h) and air flow crushed to obtain a precursor product 1 lithium ferrite.
[0066] (2) Take product 1, 5 kg of lithium ferrite and 125 g of cobalt acetate, add 10 L of deionized water, rotate and stir at 80° C. for 3 hours, centrifuge, and dry to obtain product 2, lithium ferrite coated with cobalt acetate hydroxide.
[0067] (3) Take all the product 2Cobalt acetate hydroxide-coated lithium ferrite, add 40 g of thioacetamide (TAA) and 10 L of ethanol, transfer to a 20 L high-pressure reactor, heat at 120 ° C for 10 hours, centrifuge, and dry to obtain the hydrothermal product 3CoSx-coated lithium ferrite.
[0068] (4) The hydrothermal product 3CoSx is coated with lithium ferrite and sintered at 600°C in a nitrogen atmosphere to remove the crystal water and enhance the crystallinity of the CoSx-coated lithium ferrite, thereby obtaining the final product 4CoSx-coated lithium ferrite.
[0069] Example 2
[0070] Preparation of MoS2-coated lithium ferrite
[0071] (1) According to the molar ratio of lithium to iron being 5:1, lithium carbonate and ferric nitrate are fully ground and mixed in 2-3 times the mass of water to make D90 less than 150nm to obtain a lithium ferrite precursor aqueous solution, which is then spray-dried, high-temperature sintered (600°C, 12h) and air flow crushed to obtain a precursor product 1 lithium ferrite.
[0072] (2) Take product 1: 5 kg of lithium ferrite, 100 g of sodium molybdate, and 200 g of thiourea, add 10 L of deionized water, transfer to a hydrothermal reactor, react at 220 °C for 20 hours, centrifuge, and dry to obtain hydrothermal product 2: lithium ferrite coated with molybdenum disulfide.
[0073] (3) The entire hydrothermal product 2 molybdenum disulfide-coated lithium ferrite is sintered at 600°C in a nitrogen atmosphere to remove crystal water and enhance the crystallinity of the MoS2-coated lithium ferrite, thereby obtaining the final product 3MoS2-coated lithium ferrite.
[0074] Example 3
[0075] Preparation of CoSx-coated lithium ferrite
[0076] (1) According to the molar ratio of lithium to iron being 5:1, lithium carbonate and ferric nitrate are fully ground and mixed in 2-3 times the mass of water to make D90 less than 150nm to obtain a lithium ferrite precursor aqueous solution, which is then spray-dried, high-temperature sintered (600°C, 12h) and air flow crushed to obtain a precursor product 1 lithium ferrite.
[0077] (2) Weigh products 1, lithium ferrite and cobalt acetate, at a molar ratio of lithium ferrite to cobalt acetate of (1:0.006), add deionized water 3 times the mass of lithium ferrite, rotate and stir at 75° C. for 4 hours, centrifuge, and dry to obtain product 2, lithium ferrite coated with cobalt acetate hydroxide.
[0078] (3) Take the product 2 cobalt acetate hydroxide-coated lithium ferrite, add thioacetamide (TAA) and ethanol 3 times the mass of the product 2 in a molar ratio of cobalt element to sulfur element of 1:1, transfer to a high-pressure reactor, heat at 110°C for 12 hours, centrifuge, and dry to obtain the hydrothermal product 3CoSx-coated lithium ferrite.
[0079] (4) The hydrothermal product 3CoSx is coated with lithium ferrite and sintered at 550°C in a nitrogen atmosphere to remove the crystal water and enhance the crystallinity of the CoSx-coated lithium ferrite, thereby obtaining the final product 4CoSx-coated lithium ferrite.
[0080] Example 4
[0081] Preparation of CoSx-coated lithium ferrite
[0082] (1) According to the molar ratio of lithium to iron being 5:1, lithium carbonate and ferric nitrate are fully ground and mixed in 2-3 times the mass of water to make D90 less than 150nm to obtain a lithium ferrite precursor aqueous solution, which is then spray-dried, high-temperature sintered (600°C, 12h) and air flow crushed to obtain a precursor product 1 lithium ferrite.
[0083] (2) Weigh products 1, lithium ferrite and cobalt acetate, at a molar ratio of lithium ferrite to cobalt acetate of (1:0.18), add deionized water 3 times the mass of lithium ferrite, rotate and stir at 85° C. for 2 hours, centrifuge, and dry to obtain product 2, lithium ferrite coated with cobalt acetate hydroxide.
[0084] (3) Take the product 2 cobalt acetate hydroxide-coated lithium ferrite, add thioacetamide (TAA) and ethanol 3 times the mass of the product 2 according to the molar ratio of cobalt element to sulfur element of 1:2, transfer to a high-pressure reactor, heat at 130°C for 8 hours, centrifuge, and dry to obtain the hydrothermal product 3CoSx-coated lithium ferrite.
[0085] (4) The hydrothermal product 3CoSx is coated with lithium ferrite and sintered at 650°C in a nitrogen atmosphere to remove the crystal water and enhance the crystallinity of the CoSx-coated lithium ferrite, thereby obtaining the final product 4CoSx-coated lithium ferrite.
[0086] Example 5
[0087] Preparation of MoS2-coated lithium ferrite
[0088] (1) According to the molar ratio of lithium to iron being 5:1, lithium carbonate and ferric nitrate are fully ground and mixed in 2-3 times the mass of water to make D90 less than 150nm to obtain a lithium ferrite precursor aqueous solution, which is then spray-dried, high-temperature sintered (600°C, 12h) and air flow crushed to obtain a precursor product 1 lithium ferrite.
[0089] (2) Lithium ferrite and sodium molybdate were weighed at a molar ratio of lithium ferrite to sodium molybdate of (1:0.004), as well as thiourea 3 times the mass of sodium molybdate, and deionized water 3 times the mass of lithium ferrite was added. The mixture was transferred to a hydrothermal reactor, reacted at 200°C for 24 hours, centrifuged, and dried to obtain a hydrothermal product 2, lithium ferrite coated with molybdenum disulfide.
[0090] (3) The hydrothermal product 2, lithium ferrite coated with molybdenum disulfide, is sintered at 550°C in a nitrogen atmosphere to remove the crystal water and enhance the crystallinity of the MoS2-coated lithium ferrite, thereby obtaining the final product 3MoS2-coated lithium ferrite.
[0091] Example 6
[0092] Preparation of MoS2-coated lithium ferrite
[0093] (1) According to the molar ratio of lithium to iron being 5:1, lithium carbonate and ferric nitrate are fully ground and mixed in 2-3 times the mass of water to make D90 less than 150nm to obtain a lithium ferrite precursor aqueous solution, which is then spray-dried, high-temperature sintered (600°C, 12h) and air flow crushed to obtain a precursor product 1 lithium ferrite.
[0094] (2) Lithium ferrite and sodium molybdate were weighed at a molar ratio of lithium ferrite to sodium molybdate (1:0.095), as well as thiourea 3 times the mass of sodium molybdate, and deionized water 3 times the mass of lithium ferrite was added. The mixture was transferred to a hydrothermal reactor, reacted at 250° C. for 16 hours, centrifuged, and dried to obtain a hydrothermal product 2, lithium ferrite coated with molybdenum disulfide.
[0095] (3) The hydrothermal product 2, lithium ferrite coated with molybdenum disulfide, is sintered at 650°C in a nitrogen atmosphere to remove the crystal water and enhance the crystallinity of the MoS2-coated lithium ferrite, thereby obtaining the final product 3MoS2-coated lithium ferrite.
[0096] Comparative Example 1
[0097] Preparation of carbon-coated lithium ferrite
[0098] (1) According to the molar ratio of lithium to iron being 5:1, lithium carbonate and ferric nitrate are fully ground and mixed in 2-3 times the mass of water to make D90 less than 150nm to obtain a lithium ferrite precursor aqueous solution, which is then spray-dried, high-temperature sintered (600°C, 12h) and air flow crushed to obtain a precursor product 1 lithium ferrite.
[0099] (2) The precursor product 1, lithium ferrite, is sintered in an air atmosphere at a temperature of 850° C. for 30 h to remove residual impurities such as moisture, carbonic acid, and nitric acid in the lithium ferrite to obtain product 2.
[0100] (3) The product 2 was sintered at 600°C in a methane atmosphere for 3 hours and then carbon-coated to obtain the product 3 carbon-coated lithium ferrite. The carbon source was CH4, and the amount of the carbon source added was 5 wt% of the mass of the lithium ferrite precursor.
[0101] Test Example 1
[0102] It should be noted that, in this test example, LiFePO4 was purchased from Shenzhen Defang Nano Technology Co., Ltd. with the item number DY-3; carbon nanotubes were purchased from Hongna New Material Technology Co., Ltd. with the item number Pas1004.
[0103] Positive electrode 1: The lithium ferrite, carbon black and PVDF coated with CoSx in Example 1 were mixed in a mass ratio of 90:5:5 and loaded into a ball mill, and N-methylpyrrolidone was used as a dispersion medium. The mixture was stirred to prepare a positive electrode slurry, which was coated on the positive electrode collector and dried and rolled to obtain a positive electrode sheet.
[0104] Positive electrode 2: The lithium ferrite, carbon black and PVDF coated with MoS2 in Example 2 were mixed in a mass ratio of 90:5:5 and loaded into a ball mill, and N-methylpyrrolidone was used as a dispersion medium. The mixture was stirred and prepared into a positive electrode slurry, which was coated on the positive electrode current collector and dried and rolled to obtain a positive electrode sheet.
[0105] Positive electrode 3: The carbon-coated lithium ferrite, carbon black and PVDF of comparative example 1 were mixed in a mass ratio of 90:5:5 and loaded into a ball mill, and N-methylpyrrolidone was used as a dispersion medium. The mixture was stirred to prepare a positive electrode slurry, which was coated on the positive electrode collector, and dried and rolled to obtain a positive electrode sheet.
[0106] Positive electrode 4: LiFePO4, carbon black, carbon nanotubes, PVDF, and lithium ferrite coated with CoSx in Example 1 were mixed in a mass ratio of 92.7:2.5:2.5:0.3:2 and loaded into a ball mill. N-methylpyrrolidone was used as a dispersion medium, and the mixture was stirred to prepare a positive electrode slurry, which was coated on the positive electrode current collector and dried and rolled to obtain a positive electrode sheet.
[0107] Positive electrode 5: LiFePO4, carbon black, carbon nanotubes, PVDF, and lithium ferrite coated with MoS2 in Example 2 are mixed in a mass ratio of 92.7:2.5:2.5:0.3:2 and loaded into a ball mill. N-methylpyrrolidone is used as a dispersion medium, and stirred to prepare a positive electrode slurry. The slurry is coated on the positive electrode collector, and the positive electrode sheet is obtained after drying and rolling.
[0108] Positive electrode 6: LiFePO4, carbon black, carbon nanotubes, PVDF, and carbon-coated lithium ferrite of Comparative Example 1 are mixed in a mass ratio of 92.7:2.5:2.5:0.3:2 and loaded into a ball mill, and N-methylpyrrolidone is used as a dispersion medium. The mixture is stirred and prepared into a positive electrode slurry, which is coated on the positive electrode current collector, and dried and rolled to obtain a positive electrode sheet.
[0109] Negative electrode 1: Graphite, PVDF (polyvinylidene fluoride), and carbon black were mixed in a mass ratio of 96:2:2, and N-methylpyrrolidone was used as a dispersion medium. The mixture was stirred and prepared into a negative electrode slurry, which was coated on the negative electrode current collector, and dried and rolled to obtain a negative electrode sheet.
[0110] 1. XRD test was performed on the materials provided in Examples 1-2 and Comparative Example 1. The results are as follows: Figure 1 shown.
[0111] 2. Lithium ferrite capacity test:
[0112] Experimental group: positive electrode 1 + negative electrode 1, positive electrode 2 + negative electrode 1;
[0113] Baseline group: positive electrode 3 + negative electrode 1;
[0114] Electrolyte: 1M LiPF6 electrolyte, the solvent is EC (ethylene carbonate):EMC (methyl carbonate):DMC (dimethyl carbonate) with a volume ratio of 1:1:1.
[0115] The experimental group and the reference group were assembled into batteries with the electrolyte, and the gram capacity of each battery was tested. The results are shown in Table 1.
[0116] Table 1
[0117] .
[0118] 3. Test of gas production, capacity and 1000-week capacity retention rate of lithium iron phosphate soft-pack batteries assembled with lithium iron oxide: first use 0.5C to fix the capacity, then use 1C room temperature cycle, and compare the discharge capacity retention rate after 1000 weeks; gas production is determined by drainage method.
[0119] Experimental group: positive electrode 4 + negative electrode 1, positive electrode 5 + negative electrode 1;
[0120] Baseline group: positive electrode 6 + negative electrode 1;
[0121] Electrolyte: 1M LiPF6 electrolyte, solvent EC:EMC:DMC volume ratio is 1:1:1.
[0122] The experimental group and the reference group were assembled into batteries with the electrolyte, and the performance of each battery was tested. The results are shown in Table 2 and Figure 2 shown.
[0123] Table 2
[0124] .
[0125] Afterwards, the hydrothermal product 3CoSx prepared in Example 1 was coated with lithium ferrite to prepare positive electrode 7 according to the method of positive electrode 4 in Experimental Example 1, and then assembled into a battery according to the same method. The performance of the prepared battery was tested, and the results are shown in Table 3.
[0126] Table 3
[0127] .
[0128] In addition, positive electrode sheets were prepared in Examples 3-6 according to the method of positive electrode 4 in Test Example 1, and then assembled into batteries according to the same method, and the above test 3 was carried out. The results showed (Table 4) that the batteries prepared in Examples 3-6 had a lower total gas production than that in Comparative Example 1, a higher initial capacity than that in Comparative Example 1, and a higher capacity retention rate after 1000 cycles than that in Comparative Example 1, as expected.
[0129] Table 4
[0130] .
[0131] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.
Claims
1. A positive electrode lithium supplement additive, characterized in that: It is lithium ferrite; The surface of the lithium ferrite is only coated with cobalt sulfide or molybdenum disulfide; The lithium ferrite is Li5FeO4; The molar ratio of cobalt element to sulfur element in the cobalt sulfide is 1:(0.75-2); If the surface of the lithium ferrite is coated with cobalt sulfide, the molar ratio of the lithium ferrite to the cobalt sulfide is 1:(0.006-0.18); If the surface of the lithium ferrite is coated with molybdenum disulfide, the molar ratio of lithium ferrite to molybdenum disulfide is 1:(0.004-0.095).
2. The positive electrode lithium supplement additive according to claim 1, characterized in that: The surface of the lithium ferrite is coated with cobalt sulfide, and the preparation method of the positive electrode lithium supplement additive comprises the following steps: a. The lithium ferrite, cobalt acetate and water are mixed, reacted under closed conditions and dried to obtain lithium ferrite coated with cobalt acetate hydroxide; b. The lithium ferrite coated with the cobalt acetate hydroxide obtained in step a is mixed with thioacetamide and ethanol for reaction, and after the reaction, the reaction product is sintered under a protective atmosphere to prepare a positive electrode lithium supplement additive.
3. The positive electrode lithium supplement additive according to claim 2, characterized in that: In step a, the reaction temperature is 75-85°C and the reaction time is 2-4h; In step b, the reaction temperature is 110-130°C and the reaction time is 8-12h; In step b, the sintering temperature is 550~650℃.
4. The positive electrode lithium supplement additive according to claim 1, characterized in that: The surface of the lithium ferrite is coated with molybdenum disulfide, and the preparation method of the positive electrode lithium supplement additive comprises the following steps: Lithium ferrite, sodium molybdate, thiourea and water are mixed for reaction, and after the reaction, the reaction product is sintered under a protective atmosphere to prepare a positive electrode lithium supplement additive.
5. The positive electrode lithium supplement additive according to claim 4, characterized in that: The reaction temperature is 200-250°C and the reaction time is 16-24h; The sintering temperature is 550-650°C.
6. Use of the positive electrode lithium supplement additive according to any one of claims 1 to 5 in the preparation of lithium ion batteries.
7. A positive electrode sheet, characterized in that: The active material layer of the positive electrode sheet contains the positive electrode lithium supplement additive according to any one of claims 1 to 5.
8. A lithium ion battery, characterized in that: The positive electrode sheet of the lithium-ion battery is the positive electrode sheet according to claim 7.
Citation Information
Patent Citations
Lithium supplementing cathode material containing Co-doped lithium ferrate and preparation thereof, and application of lithium supplementing cathode material containing Co-doped lithium ferrate
CN110518298A
Anode lithium supplement agent, anode plate and method for preparing anode lithium supplement agent
CN114050258A
Sulfide coated particle as well as preparation method and application thereof
CN107983272A
Lithium-rich material as well as preparation method and application thereof
CN117766698A